Alternative fuels from vegetable oils: innovative methods and technologies of production and usage - Kyrychenko, V.I.; Kyrychenko, V.V.; Ribun, V.S.; Skladaniuk, M.B. (Physics and Chemistry of Solid State, 2020)
Traditional methods of biofuel production using vegetable oils and aliphatic alcohols have a number of disadvantages. A new method of transesterification of vegetable oils with alkyl acetates because they act as promoters of diesel fuel combustion. A method of improving both technology of alcoholysis and esterolysis by modifying the temperature range is proposed. Chemical and technological bases of two-stage process of vegetable oil transesterification are developed. In the first stage, the oils are treated with glycerol in order to convert tri-acyl-glyceros of oil into mono-acyl-glycerols. The second stage is alcoholysis of mono-acyl-glycerols with ethanol or esterolysis of mono-acyl-glycerols with ethyl acetate. The temperature range of the transesterification process is improved using heat-transfer solvents. Comparison of material balances of technologies of one- and two-stage ways of ethanolysis and esterolysis showed a significant increase in the selectivity of the process, yield and quality of biofuels. Analysis of the obtained biofuels and mixtures, which contain 20 % of biofuels and 80% of diesel fuel showed the best physical, chemical and operational characteristics. Therefore, the blended fuels are promising area of ​​biofuel technology.